A Fenton treatment process without the need for external chemicals and without sludge generation

Through the combination system of biological electrical synthesis H2O2 solid -state reactor and UV activation H2O2 reactor, the problem of large and iron mud generated by FENTON craftsmanship Chinese pharmaceutical agents has been solved, and efficient organic pollutants with no agent and sludge -free and sludge -free.

CN118929890BActive Publication Date: 2025-01-28NANJING UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411421139.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-28
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The existing Fenton process has problems such as large amount of drug consumption and large amount of iron sludge production, which is difficult to effectively solve.

Method used

The combination system of biological electrical synthesis H2O2 solid -state reactor and UV activation H2O2 reactor is used to form an H2O2 solution through microbial anode room and solid electrolyte layer, and activate • Oh in UV light to achieve the removal of organic pollutants.

Benefits of technology

In the case of realizing the production of external drugs and sludge -free, the organic pollutants in the wastewater are efficiently removed, especially the removal rate of ciprobut star in the hospital's wastewater reached 95%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118929890B_ABST
    Figure CN118929890B_ABST
Patent Text Reader

Abstract

The present invention discloses a Fenton treatment process that does not require external agents and does not generate sludge, and belongs to the technical field of wastewater treatment. The Fenton treatment process is composed of a bio-electrosynthesis H2O2 solid reactor and a UV-activated H2O2 reactor. First, the microbial anode of the bio-electrosynthesis H2O2 solid reactor removes biodegradable organic matter in the wastewater, and at the same time, the air diffusion cathode electro-reduces oxygen to produce H2O2 solution; then, the UV-activated H2O2 reactor uses the synthesized H2O2 solution to generate •OH, and •OH oxidizes the biodegradable organic pollutants in the effluent of the microbial anode, thereby achieving the removal of biodegradable and biodegradable organic pollutants in the wastewater. The Fenton treatment process of the present invention is used for hospital wastewater treatment, which can not only efficiently remove antibiotics such as ciprofloxacin without the need for external agents, but also avoids the sludge generation of the traditional Fenton treatment process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an electro-Fenton treatment process which does not require external chemicals and does not generate sludge, and belongs to the technical field of wastewater treatment. Background Art

[0002] Advanced oxidation technology based on hydroxyl radicals (•OH) has been widely used in biochemical tailwater deep treatment and industrial wastewater pretreatment. This is mainly because •OH has a very strong oxidizing ability (+2.8V vs. SHE), which can effectively decompose most of the difficult-to-degrade organic pollutants. However, the Fe 2+ / Fe 3+ The obstruction of circulation will cause the process of Fenton technology to produce •OH to have problems such as high reagent consumption and large iron sludge production. According to the "Technical Specifications for Fenton Oxidation Wastewater Treatment Engineering (HJ 1095-2020)", the H2O2 dosage is twice the theoretical value, and the FeSO4 dosage is 5 times the theoretical value. This is mainly due to the fact that Fe 2+ Oxidation reaction rate (76M -1 s -1 ) is much larger than Fe 3+ Restore (0.01M - 1 s -1 ) reaction rate, which will cause Fe 3+ Although the accumulation of Fe in the Fenton reaction can be alleviated by light, electricity and the addition of chelating agents, 3+ However, H2O2, FeSO4 and other reagents still need to be continuously added during the reaction process, which cannot fundamentally solve the problems of high reagent consumption and high iron sludge production in the Fenton process. Summary of the invention

[0003] Purpose of the invention: The purpose of the present invention is to provide a Fenton treatment process, which can not only maintain excellent organic pollutant removal effect, but also solve the problems of large reagent consumption and large iron sludge generation in the existing Fenton process.

[0004] Technical solution: The Fenton treatment process described in the present invention is based on the following system, which is composed of a bio-electrosynthesis H2O2 solid reactor and a UV-activated H2O2 reactor; the bio-electrosynthesis H2O2 solid reactor includes a microbial anode chamber, a solid electrolyte layer and an air diffusion cathode; the microbial anode chamber and the solid electrolyte layer of the bio-electrosynthesis H2O2 solid reactor are separated by a cation exchange membrane, the air diffusion cathode and the solid electrolyte layer are separated by an anion exchange membrane, and the air diffusion cathode is supplied with oxygen through an aeration device; the UV-activated H2O2 reactor includes an ultraviolet lamp and a sleeve; the effluent from the anode chamber in the bio-electrosynthesis H2O2 solid reactor and the H2O2 solution formed by the solid electrolyte layer flow into the UV-activated H2O2 reactor.

[0005] The working process of the system of the present invention is: wastewater is pumped into the microbial anode chamber of the bio-electrosynthesis H2O2 solid reactor, air is passed into the air diffusion cathode of the bio-electrosynthesis H2O2 solid reactor, and a H2O2 solution is formed in the solid electrolyte layer under an applied voltage; then, the effluent from the anode chamber in the bio-electrosynthesis H2O2 solid reactor and the H2O2 solution formed by the solid electrolyte layer flow into the UV-activated H2O2 reactor, and H2O2 produces •OH under the activation of ultraviolet light, and •OH oxidizes the difficult-to-biodegrade organic pollutants in the effluent from the anode chamber, thereby jointly removing the biodegradable and difficult-to-biodegrade organic pollutants in the wastewater.

[0006] Wherein, the microbial anode is a carbon felt or carbon brush loaded with a complex of activated sludge and multi-walled carbon nanotubes. Adding multi-walled carbon nanotubes to the bioanode can significantly improve the performance of the microbial anode. The high conductivity of multi-walled carbon nanotubes constructs an efficient electron transfer network, which not only speeds up the electron transfer rate of microorganisms to the anode, but also increases the effective surface area of ​​the anode; the three-dimensional network structure formed by multi-walled carbon nanotubes not only provides more microbial attachment points, but also constructs a stable electron transfer network, which is crucial to improving the long-term stability and efficiency of the microbial anode. In this way, the electrons generated by microorganisms that could not be directly contacted on the anode surface can also be captured and utilized, thereby improving the utilization rate of microorganisms and the overall performance of the solid-state reactor for bio-electrosynthesis of H2O2.

[0007] The carbon felt loaded with the activated sludge and multi-walled carbon nanotube composite or the carbon brush loaded with the activated sludge and multi-walled carbon nanotube composite is prepared by the following method, and the specific steps are as follows:

[0008] (1) adding multi-walled carbon nanotubes to N-methylpyrrolidone and subjecting the mixture to ultrasonic treatment to form a uniform multi-walled carbon nanotube dispersion; wherein the concentration of the multi-walled carbon nanotube dispersion is 0.5-1.0 g / L; and the ultrasonic treatment time is 4.0-6.0 h;

[0009] (2) Adding glass microbeads to the activated sludge from the microbial fuel cell reactor and shaking to form a uniform activated sludge dispersion; wherein the MLSS of the activated sludge is 1.0-100 g / L; and the average diameter of the glass microbeads is 10-1000 μm;

[0010] (3) Adding the activated sludge dispersion dropwise to the stirred multi-walled carbon nanotube dispersion, mixing and centrifuging to form a composite of activated sludge and multi-walled carbon nanotubes; wherein the volume ratio of the multi-walled carbon nanotube dispersion to the activated sludge dispersion is 1:0.5-1:100; the dropping speed of the activated sludge dispersion is 0.1-100 mL / min; and the centrifugal speed after mixing is 3000-10000 rpm;

[0011] (4) The activated sludge and multi-walled carbon nanotube complex were mixed with culture medium, and then added into a bioelectrosynthesis H2O2 solid reactor for acclimation and biofilm growth for 7 days to form carbon felt loaded with the activated sludge and multi-walled carbon nanotube complex or carbon brush loaded with the activated sludge and multi-walled carbon nanotube complex; the formula of the culture medium was: 1.0 g / L sodium acetate, 50 mM phosphate buffer solution (PBS), 5.0 mL / L vitamin solution and 12.5 mL / L trace mineral solution; the acclimation voltage was 0.4~1.0 V.

[0012] The solid electrolyte layer is composed of tightly packed polymer microspheres containing quaternary ammonium groups (including but not limited to DOWEX 1×2, DOWEX 1×4, DOWEX 1×8, Amberlite IRA-400, Diaion SA10A, 201×7 and other gel-type anion exchange resins). The solid electrolyte layer contains quaternary ammonium groups that can transfer anions, and the HO2 generated by the air cathode - and OH - Under the action of the electric field, it migrates to the anode and interacts with H + Combine to form a H2O2 solution.

[0013] The air diffusion cathode is a carbon fiber membrane loaded with carbon black or a carbon cloth loaded with carbon black. The air diffusion cathode does not need to be fed with pure oxygen, but only needs to be fed with air to react and produce HO2 - and OH - .

[0014] The carbon black-loaded carbon fiber membrane or carbon black-loaded carbon cloth is prepared by the following method: spraying a carbon black dispersion onto a hydrophobic carbon fiber membrane or carbon cloth; wherein the carbon black loading on the carrier is 0.46-5.0 mg / cm 2 .

[0015] The carbon black dispersion is prepared by the following method: adding carbon black and Nafion 117 solution (mass fraction of 5%) to anhydrous ethanol to obtain a mixed solution; ultrasonicating the mixed solution for not less than 4.0 hours to form a uniform catalyst dispersion without wall adhesion. The catalyst dispersion is added to a spray gun and sprayed on a hydrophobic carbon fiber membrane or carbon cloth, and then placed in a 60°C vacuum oven for drying to obtain an air diffusion cathode loaded with carbon black.

[0016] Among them, the operating voltage of the bio-electrosynthesis H2O2 solid-state reactor is 0.2~1.0 V.

[0017] Among them, the water effluent from the anode chamber in the bio-electrosynthesis H2O2 solid reactor and the H2O2 solution produced by the solid electrolyte layer are mixed in a volume ratio of 50-200:1 and flow into the UV-activated H2O2 reactor.

[0018] Among them, the operating voltage of the bio-electrosynthesis H2O2 solid-state reactor is 0.2~1.0 V.

[0019] Among them, the hydraulic retention time of wastewater in the bio-electrosynthesis H2O2 solid-state reactor is 5~20 h; the hydraulic retention time of wastewater in the UV-activated H2O2 reactor is 10~60 min.

[0020] The working principle of the bio-electrosynthesis H2O2 solid reactor (MBES) in the system of the present invention is as follows:

[0021] Biodegradable organic pollutants in wastewater are decomposed at the bioanode to release electrons, H + The electrons are transferred to the external circuit through the anode interface and then reach the air diffusion cathode, where the carbon black catalyst reduces the oxygen to HO2. - and OH - ; Finally, under the electric field driving, H + Crossing the cation exchange membrane, HO2 - and OH - It crosses the anion exchange membrane and combines in the solid electrolyte layer to form a H2O2 solution. The standard electrode potential of the two half reactions shows that the electromotive force of MBES is greater than 0, which indicates that MBES can react spontaneously. Therefore, MBES can realize the in-situ synthesis of H2O2 solution in the wastewater treatment process:

[0022] Anode half reaction:

[0023]

[0024] Cathode half reaction:

[0025]

[0026] The working principle of the UV activated H2O2 reactor (UV / H2O2) in the system of the present invention is as follows: the effluent from the anode chamber of the bio-electrosynthetic H2O2 solid reactor and the H2O2 solution formed by the solid electrolyte layer are mixed and flowed into the UV activated H2O2 reactor. H2O2 generates •OH under the activation of ultraviolet light, and •OH oxidizes the difficult-to-biodegrade organic pollutants in the effluent from the anode chamber, thereby achieving the removal of biodegradable and difficult-to-biodegrade organic pollutants in the wastewater. Therefore, the Fenton treatment process of the present invention can achieve non-Fe 2+ / Fe 3+ The circulating H2O2 is activated, so that the whole system does not need to add external chemicals and no sludge is generated.

[0027] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: the Fenton treatment process of the present invention achieves a 95% removal rate of ciprofloxacin in hospital wastewater by bio-electrosynthesis of H2O2 and then serially activates H2O2 with UV to produce •OH; the present invention realizes in-situ bio-electrosynthesis of 20mg / L H2O2 solution in the sewage treatment process through wastewater and air at a low voltage of 0.3V, thereby avoiding the consumption of chemical reagents in the traditional Fenton technology; at the same time, under UV activation, non-Fe 2+ / Fe 3+ The circulation method realizes the activation of H2O2 to produce •OH, avoiding the production of iron sludge in traditional Fenton technology, thus solving the problems of large reagent consumption and large iron sludge production in the existing Fenton technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is the reaction principle diagram of the treatment process of the present invention;

[0029] Figure 2 It is a structural principle diagram of the treatment process of the present invention;

[0030] Figure 3 The performance of the solid-state reactor for bio-electrosynthesis of H2O2 of the present invention; wherein A is the variation trend of Faraday efficiency and inter-cell voltage with current density; B is the yield of H2O2 at different current densities:

[0031] Figure 4 is the performance of the UV activated H2O2 reactor of the present invention; wherein A is the removal rate of CIP in simulated hospital wastewater at different H2O2 addition concentrations; B is the removal rate of CIP in simulated hospital wastewater at different H2O2 addition concentrations for CIP with the same initial concentration and the same treatment time. DETAILED DESCRIPTION

[0032] like Figure 1~2As shown, the Fenton treatment process of the present invention is composed of a bio-electrosynthesis H2O2 solid reactor 1 and a UV-activated H2O2 reactor 2; the bio-electrosynthesis H2O2 solid reactor 1 includes a microbial anode 3, a solid electrolyte layer 6 and an air diffusion cathode 4, the anode chamber and the solid electrolyte layer 6 of the bio-electrosynthesis H2O2 solid reactor 1 are separated by a cation exchange membrane 5, the cathode chamber and the solid electrolyte layer 6 are separated by an anion exchange membrane 7, and the cathode chamber is also connected to an aeration device 11; the microbial anode 3 and the air diffusion cathode 4 are electrically connected to an external power supply; the UV-activated H2O2 reactor 2 includes an ultraviolet lamp 8 and a sleeve, and the ultraviolet lamp 8 is electrically connected to an external power supply; the H2O2 solution formed by the effluent from the anode chamber of the bio-electrosynthesis H2O2 solid reactor 1 and the solid electrolyte layer 6 flows into the UV-activated H2O2 reactor 2.

[0033] The bio-electrosynthesis H2O2 solid reactor 1 is used to degrade some biodegradable organic pollutants and synthesize H2O2 solution. First, the wastewater is passed into the anode chamber of the bio-electrosynthesis H2O2 solid reactor 1, and some biodegradable organic pollutants are removed, while H2O2 solution is produced. + and e - .H + Entering the solid electrolyte layer 6 through the cation exchange membrane 5; e - The O2 in the air is transferred to the air diffusion cathode 4 through the external circuit, and the O2 in the air is obtained at the air diffusion cathode 4. - , generating HO2 - and OH - Finally, HO2 - and OH - Driven by the electric field force, H2 enters the solid electrolyte layer 6 through the anion exchange membrane 7 and passes through the cation exchange membrane 5. + Combine to form H2O2 solution.

[0034] The H2O2 solution formed by the effluent from the anode chamber and the solid electrolyte layer 6 in the bio-electrosynthesis H2O2 solid reactor 1 flows into the UV-activated H2O2 reactor 2, and H2O2 produces •OH under the activation of the ultraviolet lamp, and •OH oxidizes the difficult-to-biodegrade organic pollutants in the effluent from the anode chamber, thereby realizing the removal of biodegradable and difficult-to-biodegrade organic pollutants in the wastewater by the process of the present invention.

[0035] The bio-electrosynthesis H2O2 solid-state reactor 1 is made of organic glass, and its dimensions are 16×8×8 cm (length×width×height).

[0036] The bio-electrosynthesis H2O2 solid reactor 1 is divided into three functional areas. The first part is the anode chamber, which is 8×8×8 cm (length×width×height). The microbial anode material is a carbon brush loaded with a composite of activated sludge and multi-walled carbon nanotubes, which is 5×6 cm (diameter×length). The second part is the solid electrolyte layer 6, which is 8×8×1 cm (width×height×thickness). The solid electrolyte layer 6 is filled with polymer microspheres containing quaternary ammonium groups (polymer microspheres containing quaternary ammonium cation groups on the surface) as solid electrolytes. The anode chamber and the solid electrolyte layer 6 are separated by a cation exchange membrane 5. The third part is the gas diffusion cathode 4, which is 8×8×0.01 cm. The air diffusion cathode 4 is a carbon cloth loaded with carbon black (the loading amount of catalyst carbon black on the carbon cloth is 3.0 mg / cm 2 ), the gas diffusion cathode 4 is separated from the solid electrolyte layer 6 by an anion exchange membrane 7.

[0037] The UV activated H2O2 reactor is mainly composed of an ultraviolet lamp 8 and a sleeve, wherein the sleeve has a diameter of 5.0 cm and a length of 22 cm. The ultraviolet lamp 8 has a diameter of 2.0 cm and a length of 22 cm.

[0038] In this embodiment, the carbon brush loaded with the activated sludge and multi-walled carbon nanotube composite is prepared by the following method, the specific steps are:

[0039] (1) 30 mg of multi-walled carbon nanotubes were added to 30 mL of N-methylpyrrolidone and ultrasonicated for 4 h to form a 1.0 g / L uniform multi-walled carbon nanotube dispersion;

[0040] (2) 30 mL of activated sludge was taken from the microbial fuel cell reactor, glass beads with an average diameter of 200 μm were added thereto, and the activated sludge was dispersed by shaking to form a uniform activated sludge dispersion, wherein the MLSS of the activated sludge was 10 g / L;

[0041] (3) Adding the activated sludge dispersion dropwise to the stirred multi-walled carbon nanotube dispersion at a rate of 1.0 mL / min, mixing and centrifuging to form an activated sludge and multi-walled carbon nanotube complex; wherein the volume ratio of the multi-walled carbon nanotube dispersion to the activated sludge dispersion is 1:1, and the centrifugal speed after mixing is 6000 rpm;

[0042] (4) preparing 500 mL of culture medium, wherein the formula of the culture medium is 1.0 g / L sodium acetate, 50 mM phosphate buffer solution (PBS), 5.0 mL / L vitamin solution and 12.5 mL / L trace mineral solution (favorable to microbial growth); adding the activated sludge and multi-walled carbon nanotube complex obtained in step (3) into 500 mL of culture medium and mixing evenly; then adding the mixture into a bioelectrosynthesis H2O2 solid reactor using a carbon brush as a microbial anode for 7 days of acclimatization and biofilm growth to form a carbon brush loaded with the activated sludge and multi-walled carbon nanotube complex.

[0043] The air diffusion cathode is prepared by the following method, specifically:

[0044] (1) Add 32 mg of carbon black and 80 μL of Nafion 117 solution (mass fraction 5%) into 8.0 mL of anhydrous ethanol to obtain a mixed solution;

[0045] (2) ultrasonically treating the mixed solution for 4.0 h to form a uniform carbon black dispersion without wall adhesion;

[0046] (3) Add the carbon black dispersion into the spray gun and spray it on the carbon cloth. After spraying, put it into a 60°C vacuum oven for drying to obtain an air diffusion cathode loaded with carbon black.

[0047] The water quality of hospital wastewater is complex, mainly containing a variety of residual antibiotics, including quinolones (ciprofloxacin, ofloxacin, norfloxacin), sulfonamides (sulfamethoxazole, trimethoprim, sulfamethoxazole). First, the simulated hospital wastewater (the initial CIP concentration in the wastewater was 10 mg / L) was pumped into the microbial anode chamber of the bioelectrosynthesis H2O2 solid reactor to remove biodegradable organic pollutants. Then, air was exposed to the air diffusion cathode of the bioelectrosynthesis H2O2 solid reactor at different current densities (0.5, 1.0, 1.5 and 2.0 mA cm -2 ) forms a H2O2 solution in the lower solid electrolyte layer.

[0048] By measuring the H2O2 production at different current densities, the Faraday efficiency and H2O2 concentration of the solid-state reactor for bio-electrochemical H2O2 synthesis were calculated. Figure 3 As shown in Figure 2, the Faraday efficiency decreases with increasing current density, while the cell voltage increases with increasing current density. -2 At the current density of 2.0 mA cm, the Faraday efficiency of the air diffusion cathode reached more than 80%, and the H2O2 concentration produced by the solid electrolyte layer was ~18 mg / L. -2 At the current density, the Faraday efficiency of the air diffusion cathode is ~75%, and the H2O2 concentration produced by the solid electrolyte layer reaches ~65 mg / L.

[0049] Next, the H2O2 solution formed by the effluent from the anode chamber and the solid electrolyte layer in the bioelectrosynthesis H2O2 solid reactor flows into the UV-activated H2O2 reactor, where the hydraulic retention time of the effluent from the anode chamber in the UV-activated H2O2 reactor is 60 min; finally, H2O2 produces •OH under the activation of ultraviolet light, and •OH oxidizes the difficult-to-biodegrade organic pollutants in the effluent from the anode chamber, thereby jointly removing biodegradable and difficult-to-biodegrade organic pollutants in hospital wastewater.

[0050] By measuring the concentration of residual ciprofloxacin (CIP) in simulated hospital wastewater at different H2O2 addition concentrations (i.e., the H2O2 solution formed by the anode chamber effluent and the solid electrolyte layer in the bio-electrosynthesis H2O2 solid reactor is mixed in different volume ratios and sent to the UV-activated H2O2 reactor), the removal rate of CIP, a difficult-to-biodegrade organic pollutant, was calculated. The results are shown in Figure 4 As shown, at a concentration of 10 mg / L H2O2, the removal rate of CIP in the simulated hospital wastewater is as high as 95%; at a concentration of 60 mg / L H2O2, the removal rate of CIP in the simulated hospital wastewater is as high as 96%. Therefore, the Fenton treatment process of the present invention can be applied to the treatment of hospital wastewater, and can achieve efficient removal of antibiotics such as ciprofloxacin without adding external agents, while avoiding the generation of sludge in the traditional Fenton treatment process.

Claims

1. A Fenton treatment process without the need for external chemicals and without sludge generation, characterized in that: The treatment process is based on the following system, which is composed of a bio-electrosynthesis H2O2 solid reactor (1) and a UV-activated H2O2 reactor (2); the bio-electrosynthesis H2O2 solid reactor (1) comprises a microbial anode (3), a solid electrolyte layer (6) and an air diffusion cathode (4); the anode chamber and the solid electrolyte layer (6) of the bio-electrosynthesis H2O2 solid reactor (1) are separated by a cation exchange membrane (5), and the cathode chamber and the solid electrolyte layer (6) are separated by an anion exchange membrane (7); the cathode chamber is also connected to an aeration device (11); the microbial anode (3) and the air diffusion cathode (4) are electrically connected to an external power source; the UV-activated H2O2 reactor (2) comprises a casing and an ultraviolet lamp (8) fixed in the casing; the effluent from the anode chamber of the bio-electrosynthesis H2O2 solid reactor (1) and the H2O2 solution formed by the solid electrolyte layer (6) are mixed and then flow into the UV-activated H2O2 reactor (2); The microbial anode (3) is a carbon felt or a carbon brush loaded with a composite of activated sludge and multi-walled carbon nanotubes. The carbon felt or the carbon brush loaded with the composite of activated sludge and multi-walled carbon nanotubes is prepared by the following method, which comprises the following specific steps: (1) adding multi-walled carbon nanotubes to N-methylpyrrolidone and subjecting the composite to ultrasonic treatment to form a uniform multi-walled carbon nanotube dispersion. The concentration of the multi-walled carbon nanotube dispersion is 0.5-1.0 g / L. The ultrasonic treatment time is 4.0-6.0 h. (2) adding glass beads to the activated sludge from the microbial fuel cell reactor and subjecting the activated sludge to a vortex treatment to form a uniform activated sludge dispersion. The MLSS of the activated sludge is 1.0-100. g / L; the average diameter of the glass beads is 10~1000μm; (3) adding the activated sludge dispersion dropwise to the stirred multi-walled carbon nanotube dispersion, mixing and centrifuging to form an activated sludge and multi-walled carbon nanotube complex; wherein the volume ratio of the multi-walled carbon nanotube dispersion to the activated sludge dispersion is 1:0.5~1:100; the drop rate of the activated sludge dispersion is 0.1~100 mL / min; the centrifugal speed after mixing is 3000~10000 rpm; (4) mixing the activated sludge and multi-walled carbon nanotube complex with the culture medium, and then adding it to the bio-electrosynthesis H2O2 solid reactor for 7 days of acclimatization and biofilm growth to form a carbon felt loaded with the activated sludge and multi-walled carbon nanotube complex or a carbon brush loaded with the activated sludge and multi-walled carbon nanotube complex; the formula of the culture medium is: 1.0 g / L sodium acetate, 50 mM phosphate buffer solution, 5.0mL / L vitamin solution and 12.5 mL / L of trace mineral solution; The solid electrolyte layer (6) is composed of a stack of polymer microspheres containing quaternary ammonium groups or polymer microspheres containing sulfonic acid groups.

2. The Fenton treatment process according to claim 1, characterized in that: The air diffusion cathode (4) is a carbon fiber membrane or carbon cloth loaded with carbon black.

3. The Fenton treatment process according to claim 2, characterized in that: The carbon black-loaded carbon fiber membrane or carbon black-loaded carbon cloth is prepared by the following method: spraying a carbon black dispersion onto the carbon fiber membrane or carbon cloth, and drying to obtain the carbon black-loaded carbon fiber membrane or carbon black-loaded carbon cloth; wherein the carbon black loading on the carbon fiber membrane or carbon cloth is 0.46-5.0 mg / cm 2 .

4. The Fenton treatment process according to claim 3, characterized in that: The carbon black dispersion is prepared by the following method: specifically, carbon black particles and Nafion 117 solution are added into anhydrous ethanol to obtain a mixed solution; and the mixed solution is ultrasonicated for not less than 4.0 hours to form a uniform carbon black dispersion without wall adhesion.

5. The Fenton treatment process according to claim 1, characterized in that: The operating voltage of the bio-electrochemical H2O2 solid-state reactor (1) is 0.2-1.0 V.

6. The Fenton treatment process according to claim 1, characterized in that: The water effluent from the anode chamber of the bio-electrosynthesis H2O2 solid reactor (1) and the H2O2 solution produced by the solid electrolyte layer (6) are mixed at a volume ratio of 50-200:1 and flow into the UV-activated H2O2 reactor (2).

7. The Fenton treatment process according to claim 1, characterized in that: The hydraulic retention time of the wastewater in the bio-electrosynthesis H2O2 solid-state reactor (1) is 5 to 20 h; the hydraulic retention time of the wastewater in the UV-activated H2O2 reactor (2) is 10 to 60 min.

Citation Information

Patent Citations

  • Method of degrading formaldehyde based on bioelectrochemistry / advanced oxidation coupled system

    CN107670487A

  • Method for biological ex-situ degradation of formaldehyde

    CN109647154A